FOSTERING CRITICAL THINKING IN ENGLISH LEARNING: AN ANALYSIS OF ENGLISH FOR NUSANTARA TEXTBOOK - Nasution, Durratu Fakhria; Hidayat, Didin Nuruddin; Husna, Nida (Program Studi Tadris Bahasa Inggris Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
This study investigates how the “English for Nusantara” Grade IX textbook shapes students’ critical thinking skills by using a Critical Discourse Analysis (CDA). As part of Indonesia’s goals in education, English for Nusantara published by the Indonesian Ministry of Education, Culture, Research, and Technology aims to integrate local cultural values with English language learning, promoting both linguistic skills and critical thinking skills. The research focused on analyzing the discourse in the textbook, including the languages and activities, to evaluate their potential in shaping students’ critical thinking skills. This study using Ilyas’ frameworks as the main analysis to see the indicators for the critical thinking. The study examined whether the textbook contains languages or activities that promotes the indicators; there are (1) clarification; (2) assumption; (3) reasons and evidence; (4) viewpoints or perspectives; (5) implications, consequences, and alternatives; (6) questions; (7) predictions; (8) agreement and disagreement; (10) summary and conclusion. The results showed that eight out of the ten indicators of critical thinking by Ilyas were applied in this textbook. It is also found that this textbook promotes critical thinking linked with the indicators by Facione, called self-regulation.